Visualizing the Potential Impairment of Polymyxin B to Central Nervous System Through MR Susceptibility-Weighted Imaging - Zhang, Ni; Zhu, Lichong; Ouyang, Qiuhong; Yue, Saisai; Huang, Yichun; Qu, Shuang; Li, Runwei; Qiao, Yuanyuan; Xu, Man; He, Fangfei; Zhao, Bin; Wei, Lai; et al. (Frontiers in Pharmacology, 2021)
Polymyxin B (PMB) exert bactericidal effects on the cell wall of Gram-negative bacteria, leading to changes in the permeability of the cytoplasmic membrane and resulting in cell death, which is sensitive to the multi-resistant Gram-negative bacteria. However, the severe toxicity and adverse side effects largely hamper the clinical application of PMB. Although the molecular pathology of PMB neurotoxicity has been adequately studied at the cellular and molecular level. However, the impact of PMB on the physiological states of central nervous system in vivo may be quite different from that in vitro, which need to be further studied. Therefore, in the current study, the biocompatible ultra-uniform Fe3O4 nanoparticles were employed for noninvasively in vivo visualizing the potential impairment of PMB to the central nervous system. Systematic studies clearly reveal that the prepared Fe3O4 nanoparticles can serve as an appropriate magnetic resonance contrast agent with high transverse relaxivity and outstanding biosafety, which thus enables the following in vivo susceptibility-weighted imaging (SWI) studies on the PMB-treated mice models. As a result, it is first found that the blood-brain barrier (BBB) of mice may be impaired by successive PMB administration, displaying by the discrete punctate SWI signals distributed asymmetrically across brain regions in brain parenchyma. This result may pave a noninvasive approach for in-depth studies of PMB medication strategy, monitoring the BBB changes during PMB treatment, and even assessing the risk after PMB successive medication in multidrug-resistant gram-negative bacterial infected patients from the perspective of medical imaging.